Are wildcard events on infrastructure systems opportunities for transformational change?. (March 2015) - Walsh, C.L.; Glendinning, S.; Castán-Broto, V.; Dewberry, E.; Powell, M.
Highlights: Wildcard events test complex infrastructure systems. Such can be integrated in theoretical frameworks to understand transitions. Qualitative examples identify intervention points in complex infrastructure systems. Intervention points may promote changes towards a more sustainable infrastructure. Abstract: Infrastructure systems face a number of pressing challenges relating to demographics, environment, finance and governance pressures. Furthermore, infrastructure mediates the way in which everyday lives are conducted; their form and function creating a persistence of unsustainable practice and behaviour that cannot be changed even if change is desired. There is a need to find means by which this obduracy can be broken so that new, more sustainable futures can be planned. This paper develops a methodology, taking concepts from both engineering and social science. Wild cards, or physical disruptions, are used to 'destructively test' complex infrastructure systems and the multi-level perspective is used as a framework for analysing the resulting data. This methodology was used to examine a number of case studies, and with focus groups consisting of a range of different infrastructure providers and managers, to gain a better understanding of systems' socio-technical characteristics and behaviours. A number of impactful 'intervention points' emerged that offered the opportunity to promote radical changes towards configurations of infrastructure systems that provide for 'less' physical infrastructure. This paper also examines the utility of wild cards as enablers of transition to these 'less' configurations and demonstrates how a 'wild card scenario' can be used to co-design infrastructure adaptation from with both infrastructure providers and users.